Effectiveness of digital and conventional impressions used in the replacement of hard tissue defects of lateral teeth: evaluation of patient perception, treatment comfort and time spent - Kutsuk Анатолій Анатолійович (Actual Dentistry, 2024)
Introduction. The accuracy of the final impressions significantly affects the quality of the manufactured prosthesis. The transfer of perfect impressions to dental laboratories is always performed by dentists as part of the daily work of manufacturing prostheses in fixed prosthodontics. The accuracy of the impression depends on the materials themselves, the types of impression spoons and the impression technique. Various materials and printing techniques are used to obtain high-precision impressions. Goal. To conduct a comparative evaluation of the effectiveness of digital and conventional impressions used in the replacement of hard tissue defects of teeth of lateral teeth: assessment of patient perception, treatment comfort and time spent. To investigate the level of stress perceived by the patient at the stages of orthopedic treatment. Research material and methods. The study involved 46 patients aged 25-60 years (22 men and 24 women) who applied for orthopedic treatment of 57 defects of hard tissues of lateral teeth and had no previous experience of using conventional or digital impressions. The patient’s perceived source of stress was assessed using a modified version of the Norman Core test. Dental arch impressions were taken using polyester impression material, and bite registration was performed using polysiloxane bite registration material. Two weeks later, digital impressions and bite scans were performed on the same patients using an intraoral scanner. Both procedures were evaluated by the patients’ perception using a visual analogue scale (VAS). Patients’ perception of various impression-taking techniques was assessed using a standardized questionnaire. The stages of print processing (tray selection, working time, etc.) were recorded in seconds. The results. We found gender variations in psychoemotional reactions to specific dental interventions, highlighting potential psychological and emotional differences between male and female participants. the prevalence of strong and very strong fear of orthopedic surgery was slightly higher among female participants than among male participants. The average total time of obtaining a print using the traditional technique was 831.11 ± 5.56 s. It took half as much time to obtain prints using the digital method - 396.07 ± 7.98 seconds. In women, when receiving digital and conventional prints, the VAS indicators were lower than in men, which indicates a worse perception of the procedure by them. However, with the use of digital impressions, both women and men felt significantly higher VAS scores, which proved the advantage of using a digital method of obtaining impressions. The digital impression technique was most acceptable to both male and female patients and was preferred by all subjects. However, it is necessary to note the difference in the distribution of preferences between men and women. Conclusion. The results of the conducted study indicate that the effectiveness of the digital impression technique was higher than the traditional impression technique in terms of time spent on treatment, occurrence of adverse reactions, comfort and perception of subjects. Therefore, intraoral scanners are a clear advantage for patients visiting the dentist. Keywords: defects of hard dental tissues, digital and standard impressions, patients’ feelings, stress level.